2018
DOI: 10.1007/s10072-018-3396-0
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin, alarmin signaling, and copeptin: cross-talk between obesity and acute ischemic stroke initiation and severity in Egyptians

Abstract: Acute ischemic stroke (AIS) is followed by a strong inflammatory response contributing to brain damage and making early diagnosis and treatment inevitable. Hence, obesity is a state of chronic inflammation with amplified oxidative stress; this study aimed to assess the role played by thrombomodulin (TM)/alarmin signaling pathway and copeptin in AIS initiation and severity in addition to the implication of abnormal body weight. The study was conducted on 50 participants; 30 were patients with AIS (15 overweight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In recent studies, TM has been shown to reduce cerebral infarct size in stroke models [14,20]. Compared to other anticoagulants, the risk of bleeding appears to be lower in animals and humans treated with sTM, suggesting its protective role in preventing brain damage in stroke [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent studies, TM has been shown to reduce cerebral infarct size in stroke models [14,20]. Compared to other anticoagulants, the risk of bleeding appears to be lower in animals and humans treated with sTM, suggesting its protective role in preventing brain damage in stroke [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth discussing the contrasting observation that populations with genetically determined elevated pTM levels appear to experience worse long-term vascular status, leading to increased risks of ischemic stroke and adverse clinical outcomes [14]. Hongzhou et al conducted a two-sample mendelian randomized study and demonstrated that a genetic predisposition to elevated pTM levels was associated with an increased risk of ischemic stroke [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation